(untitled) (Південний архів (історичні науки), 2024)
The purpose of the article is to examine the religious component as a means of ensuring the national security of Ukraine. One of the most acute problems of our time, in the context of the Russian-Ukrainian war, is also the problem of ensuring security in the field of religion. Underestimation of this problem can lead to a national crisis. The spiritual and religious component of any society is able to overcome crisis phenomena, change national identity, reorganize in the right direction, unite and lead the country to victory even in times of war. The methodological basis of the study is based on both general historical research methods, including analysis, synthesis, and special historical methods. At the same time, methods of sociology, such as observation, were used. A study of the influence of religious organizations on the harmonization of the spiritual life of Ukrainians, which is an important factor in the consolidation of society in overcoming the bloody enemy, was conducted. In times of full-scale war unleashed by Russia against Ukraine, an important factor in achieving victory is the creation of spiritual foundations, consolidation of society, reorientation of people’s consciousness to higher values, preservation of cultural, spiritual, and civic identification of Ukrainians. It is spiritual values that are becoming especially important and perhaps even critical for the social stability of the state and are becoming the leading factors of its sustainable development. It should be noted that in Ukraine, historically, religion as a social institution has actively contributed to the consolidation of the Ukrainian ethnos, strengthening moral foundations and ensuring social stability and solidarity. It is well known that Orthodoxy played an important role in preserving the Ukrainian national consciousness. During the national liberation struggle of B. Khmelnytsky, the defense of Orthodoxy was one of the main slogans of the Ukrainian Cossacks, with which they fought for their statehood. Conclusions. The author notes that the influence of the religious component on the formation and ensuring of national security of Ukraine. The importance of religious organizations as the basis for consolidating the spiritual life of Ukrainians was investigated and the author proved how important and undoubtedly valuable religious support for the consciousness of Ukrainians during the war was.